Response Predictors in Chronic Migraine: Medication Overuse and Depressive Symptoms Negatively Impact Onabotulinumtoxin-A Treatment - Schiano di Cola, Francesca; Caratozzolo, Salvatore; Liberini, Paolo; Rao, Renata; Padovani, Alessandro (Frontiers in Neurology, 2019)
Background: Albeit numerous studies have investigated clinical, radiological and biochemical response predictors, the clinical profile of those patients who might benefit from OnabotulinumtoxinA is still missing. Aim of the present study was to identify potential OnabotulinumtoxinA response predictors among several clinical characteristics and confirm OnabotulinumtoxinA efficacy and safety in chronic migraine (CM) prevention. Methods: The study was conducted at the Headache Centre – Neurology Clinic at the Spedali Civili Hospital of Brescia. Eighty-four consecutive CM patients were enrolled, with a mean age of 48 years (SD 9.7) and a mean disease duration of 10.1 years (SD 6.6). The mean reported headache-days frequency was 22.5 (SD 5.9) per month, while the mean number of severe headache-days was 15.2 (SD 8.9) with a mean monthly medication intake of 33.2 (SD 5.6). The clinical characteristics analyzed as potential response predictors were: gender, disease duration, migraine characteristics (location, side constancy, unilateral autonomic and neurovegetative symptoms), previous prophylactic treatments, add-on therapies, withdrawal therapies, psychiatric (anxiety and depression symptoms) comorbidities and medication overuse. Results: A significant reduction from baseline to 3, 6, 9 and 12 months treatment cycles in total headache days, high intensity headache days and triptans consumption per month was found. Depressive symptoms and medication overuse negatively predicted OnabotulinumtoxinA outcome. Conclusions: Our results confirm the efficacy and safety of OnabotulinumtoxinA in CM. Depressive comorbidity and medication overuse, among all clinical variables, were the only significant response predictors. Such findings provide interesting insights into the current state of the art regarding patients’ selection for OnabotulinumtoxinA treatment as, with the introduction of anti calcitonin gene-related (CGRP) monoclonal antibodies, clinicians will have to thoroughly judge and tailor among the many available therapeutic options now available. Future research might be needed to confirm our findings, in particular for its therapeutic implications.